Elevations in Serum Dickkopf-1 and Disease Progression in Community-Dwelling Older Adults With Mild Cognitive Impairment and Mild-to-Moderate Alzheimer’s Disease - Tay, Laura; Leung, Bernard; Yeo, Audrey; Chan, Mark; Lim, Wee Shiong (Frontiers in Aging Neuroscience, 2019)
Background: Disruption of Wnt signaling has been implicated in dysfunctional synaptic plasticity, the degree of which correlates with Alzheimer’s disease severity. We sought to examine whether serum Dickkopf-1 (Dkk-1), a Wnt antagonist, is associated with global disease progression in older adults with mild cognitive impairment (MCI) and mild-to-moderate AD. Methods: We prospectively followed 88 older adults with MCI and mild-to-moderate AD attending a Memory Clinic. Cognitive, functional performance and neuropsychological symptoms were assessed at baseline and 1-year. We reviewed neuroimaging and performed ApoE genotyping at baseline. Serum Dkk-1 was assayed at baseline and 1-year, along with blood biomarkers of inflammation and endocrine dysfunction. We defined global disease progression (“progressors”) as increase in Clinical Dementia Rating Sum-of-Boxes (CDR-SB) score by >2 points at 1-year. Results: Fifteen (17.0%) participants had global disease progression. At baseline, there was no difference in cognitive performance and neuropsychiatric symptoms, although progressors were more impaired in instrumental activities of daily living (p=0.008). Progressors had significantly greater deterioration in cognitive performance (p=0.002), with significantly worse functional performance and more severe neuropsychiatric symptoms (p=0.042) at follow-up. Serum inflammatory and endocrine biomarkers at baseline and 1-year were similar between groups. Serum Dkk-1 had increased significantly from baseline amongst progressors, while non-progressors exhibited decremental Dkk-1 (Dkk-1change: 354.304+670.467 vs -173.582+535.676ng/ml, p=0.001). Adjusting for age, gender and baseline cognitive performance, incremental Dkk-1 independently predicted global cognitive decline (p=0.012) Conclusion: Our results suggest progressively dysfunctional Wnt signaling through Dkk-1 antagonism in contributing to disease progression amongst older adults with MCI and mild-moderate AD.